ANALISIS KURS DAN PRODUKSI TEKSTIL TERHADAP IMPOR TEKSTIL DI INDONESIA - Mauliza Mauliza; Devi Andriyani (Jurnal Ekonomi Regional Unimal, 2021)
This study aims to determine the effect of exchange rates and textile production on textile imports in Indonesia. The data used in this study are secondary data obtained from the Central Bureau of Statistics and Bank Indonesia from 2009 quarter 1 to 2018 quarter 4. The data analysis method used in this study is the Multiple Linear Regression analysis method. The results show that the exchange rate variables partially has a positive and significant effect on the volume of textile imports in Indonesia. Partially, production has a positive and significant effect on the volume of textile imports in Indonesia. Simultaneously,  the exchange rate and textile production have a positive and significant effect on the volume of imports of Indonesian textiles. The magnitude of the effect of exchange rates and production on textile imports is 0.627 (62.7%), while those influenced by other variables outside this model are 0.373 (37.3%).Keywords: textile imports, exchange rates, production